PENYELESAIAN SENGKETA PERTANAHAN MELALUI JALUR MEDIASI (STUDI PADA KANTOR PERTANAHAN KABUPATEN KARAWANG) - Ade Sinta; Devi Siti Hamzah Marpaung (Al Qisthas: Jurnal Hukum dan Politik Ketatanegaraan, 2021)
Settlement of Land Disputes through Mediation (Studies on Karawang Regency Land). The Karawang Regency Land Office can resolve several cases of land disputes through mediation, but cases are rarely resolved. In this thesis, several issues are raised, namely the role of the Karawang Regency Land Office in resolving land disputes through mediation, the procedure for resolving land disputes through mediation at the Karawang Regency Land Office and what is the success rate of mediation and obstacles in the mediation process at the Karawang Regency Land Office. The research method used in this research is a combination of a normative juridical approach with an empirical juridical approach. The normative juridical approach is to collect the necessary literature in the form of books, research journals, internet sites and laws and regulations on mediation, the National Land Agency, then an empirical juridical approach, namely by collecting data which is then taken from the results of interviews with the Head of Dispute Handling Subsection. , Conflicts and Land Cases. Settlement of land disputes at the Karawang Regency Land Office through mediation, which acts as a mediator. Settlement of land disputes through several procedures that have been implemented at the Karawang Regency Land Office. The success rate of resolving land disputes through mediation is rarely resolved, this is influenced by several obstacles. After conducting the research, it was concluded that the role of the Karawang Regency Land Office in resolving land disputes through mediation as a mediator was not optimal. Dispute resolution carried out at the Karawang Regency Land Office is carried out in accordance with Technical Guidelines No..05 / Juknis / D.V / 2007 concerning Mediation Implementation Mechanisms and Regulation of the Minister of Agrarian Affairs Number 11 of 2016 concerning Settlement of Land Cases. The success rate of mediation at the Karawang Regency Land Office is very low. This level of success is influenced by obstacles in the mediation process from the disputing parties which brings more emotional feelings, if the disputing parties use the services of a legal attorney, then there are some attorneys who prefer to win cases in court, and the absence of one of the parties in the mediation process.